user-friendly interaction with data as exemplified using pharmacological package- insert textbases - Varughese, Alvin Joseph (My University, 2007)
The Medical field is vast and dynamic. To be effective in their professions, doctors are required to keep track of the constant growth in knowledge that is taking place, although it is unrealistic to expect them to do so fully. The knowledge in this field is inherently descriptive and thus an unlikely candidate for storage in traditional databases, but instead are found in textbases. In spite of the limitations of databases, they are still used in the medical profession as they remain the standard means of storing information. The aim of this study was to demonstrate that it is possible to provide a single interface to medical knowledge in its more natural form, a textbase. This was achieved by investigating the relevant areas, creating models for the various elements of the system, and subsequently constructing such a system for demonstration. Through the use of data interaction models, this work shows that the doctor’s knowledge can be adequately supplemented, as validated by testing, enabling them to make correct decisions using the information provided. Thus the opportunity exists to implement the methodology in other areas where descriptive knowledge exists.
Student Number : 9808961X - MSc research report - School of Electrical and Information Engineering - Faculty of Engineering and the Built Environment
Keywords: data interaction; pharmacology; textbases